2021
DOI: 10.3390/app11041414
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Plant Electrophysiology Signals for Detection of Spider Mites Infestation in Tomatoes

Abstract: Herbivorous arthropods, such as spider mites, are one of the major causes of annual crop losses. They are usually hard to spot before a severe infestation takes place. When feeding, these insects cause external perturbation that triggers changes in the underlying physiological process of a plant, which are expressed by a generation of distinct variations of electrical potential. Therefore, plant electrophysiology data portray information of the plant state. Analyses involving machine learning techniques applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Recent work [13] has demonstrated the possibility of acquiring continuous and stable long-term plant electrophysiology signals in typical greenhouse conditions. Further studies have shown that the signal recordings encode discriminative patterns for stress related to drought [13] and to the presence of spider mites [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work [13] has demonstrated the possibility of acquiring continuous and stable long-term plant electrophysiology signals in typical greenhouse conditions. Further studies have shown that the signal recordings encode discriminative patterns for stress related to drought [13] and to the presence of spider mites [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent exploratory study on plant electrophysiology, introduces a methodology to classify the plant state related to the applied stimulus with an accuracy of 80% [14]. However, the related process of feature calculation i.e., extraction of the information from the recorded signal for transforming the raw signal data into a form on which the modelling of a classifier could be applied, is a time-consuming task which limits the potential use and benefits of this framework in daily agricultural practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to make the detection autonomous, several studies have been developed in the last years. Different techniques such as image processing-based detection [15][16][17][18][19][20], capacitive sensors [21,22], radar techniques [23], optoelectronics [24], electrophysiological signals [25] and acoustic-and optoacoustic-based detection methods [26][27][28][29][30][31] have been proposed and tested in the field. Nevertheless, most of these technologies use post-processing in order to detect the pest and only a few of them use real-time processing of the information acquired and energy optimization for field conditions [21,22,32,33].…”
Section: Introductionmentioning
confidence: 99%